A comparative analysis of workload and career progression of faculty members in Uganda’s private and public universities - Eva Irene, Tumusiime (Kabale University Interdisciplinary Research Journal, 2022)
Career progression is a goal most employees, particularly faculty members, pursue to improve job satisfaction and advance towards self-actualisation. However, many faculty members in Uganda’s private and public universities are lagging behind their desired level of career progression, but how this situation is explained by the workload allocated to them has not been comparatively analysed. The cross-sectional design was used to assess the effect of workload on academic staff career progression. Data on 207 lecturers randomly selected from two private and two public universities using the heterogeneous purposive sampling was used. Results from linear regression analysis indicate that workload assigned in terms of teaching tasks, is a significant constraint to lecturers’ career progression. Much of the time lecturers would have used to improve their careers through research, publication and further training is spent on teaching. Results from independent samples T-test show that this scenario is more pronounced in public than private universities because of understaffing caused by underfunding of these universities. The paper concludes public universities’ should improve staffing levels to address workload allocation in way that creates times for faculty members to pursue career.